SOSIALISASI PERENCANAAN KEUANGAN KELUARGA PADA IBU RUMAH TANGGA DAN ANGGOTA PEMBERDAYAAN KESEJAHTERAAN KELUARGA - Denia Maulani; Syakira Rezky Ananda (JPMUJ, 2025)
Financial planning is an important part of financial management, especially for households and members of the Family Welfare Empowerment (PKK). The purpose of this socialization is to provide understanding and knowledge to housewives and Family Welfare Empowerment Association members in Bojongnangka Village, Bogor Regency. The method is carried out in 3 stages, namely the planning and preparation stage, the implementation stage, and the evaluation stage. The results obtained by the audience through the presentation of the material that has been carried out are the housewives understand more that family financial planning is very important and are motivated to make family financial planning such as making a budget, and keeping records of expenses and income. This socialization activity is expected to be useful and provide more knowledge to housewives in Bojongnangka Village in handling family finances by making family financial planning.